RESPONSABILIDADE CIVIL NO CASO DAS MORTES EM PRESÍDIOS AMAZONENSES EM MAIO DE 2019 (Reflection and Critique Law Magazine, 2020)
Between May 26 and 27, 2019, fifty-six inmates detained in four prison complexes in the state of Amazonas were murdered inside their cells by inmates belonging to a rival criminal faction. Although indirectly the Governor of Amazonas state blamed on the company UmanizzareGestãoPrisional e Serviços Ltda., while the president of the TJAM  stated that there was no State responsibility in the face of surprise and inevitability. In this article, we investigated the attribution of civil responsibility for the massacre that occurred, using the hypothetical-deductive method, based on the assumption of objective civil responsibility of the State, examining the evolution of State responsibility, bidding documents, terms of contracts with the co-managerprivate company, the basic projects, the pertinent legislation and the position of some authors on the subject. It was concluded by the confirmation of the hypothesis proposed.